2005
DOI: 10.1681/asn.2004070581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Balance and the Combination of Ultrafiltration Profile during Sodium Profiling Hemodialysis on the Maintenance of the Quality of Dialysis and Sodium and Fluid Balances

Abstract: Excessive sodium gain is a major hindrance of sodium profiling hemodialysis (HD) that offsets the benefit in reducing intradialytic hypotension-related discomforts (IHD). Patients who showed frequent IHD (>30% of the sessions; n ‫؍‬ 11) were enrolled in a prospective study that consisted of two phases. In the phase 1 study, eight treatment modalities were evaluated: Conventional HD (control), sodium balance-positive step-down sodium profiling HD (PS), sodium balance-neutral stepdown sodium profiling HD (NS), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
94
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 25 publications
3
94
0
3
Order By: Relevance
“…30 Sodium gain may arise even at standard dialysate sodium (ie, 140 mEq/L) when patients start dialysis with a lower serum sodium concentration (ie, <140 mEq/L). 31 Apart from raising interdialytic weight gain and BP, this positive sodium gradient may be of particular importance in pathogenesis of intradialytic hypertension.…”
Section: Sodiummentioning
confidence: 99%
“…30 Sodium gain may arise even at standard dialysate sodium (ie, 140 mEq/L) when patients start dialysis with a lower serum sodium concentration (ie, <140 mEq/L). 31 Apart from raising interdialytic weight gain and BP, this positive sodium gradient may be of particular importance in pathogenesis of intradialytic hypertension.…”
Section: Sodiummentioning
confidence: 99%
“…Time-averaged dialysate sodium concentrations are generally higher with sodium profiling as compared to dialysis with a fixed dialysate sodium concentration. Not surprisingly, these sodium balance-positive profiles are associated with increased interdialytic symptoms, such as thirst and weight gain [41] . Therefore, there is no role for long-term use of sodium profiling with a positive sodium balance in clinical practice.…”
Section: Avoidance Of Inappropriate Sodium Profilingmentioning
confidence: 99%
“…Recent studies suggest this approach is particularly effective when combined with sodium modeling. 7,8 Devices to monitor intradialytic changes in blood volume have been advocated as a tool to minimize intradialytic hypotension on the basis of the concept that the likelihood of developing hypotension will always occur at roughly the same reduction of blood volume. Unfortunately, most studies have not found a close relationship between individual changes in blood volume and occurrence of hypotension.…”
mentioning
confidence: 99%